Perception of japanese language students on role-play as assessment instrument / Nur Anisah Tan Abdullah …[et al.] - Tan Abdullah, Nur Anisah; Husin, Norhazlina; Awang Boon, Mohd Hassan; Md Noor, Simah (Universiti Teknologi MARA, 2020)
Role-playing is an effective technique in teaching and learning a third language. This technique can not only help achieve learning objectives but also increase interest among students. At the same time, the role play can be used as one of the evaluation instruments. A case study of 253 students taking Japanese as a third language course was conducted. A set of survey questions consisting of three (3) sections is given to students to (i) assess students' readiness to undergo role-playing tests as an assessment instrument in Japanese language teaching, (ii) evaluate the effectiveness of items tested in role-playing and (iii ) provide an opportunity for students to provide suggestions for improvement on the assessment instruments conducted. The results of the study found that most students agreed that role playing (i) is able to test students' language skills, (ii) improve speaking skills, (iii) increase confidence to write in Japanese, (iv) enable better interaction in Japanese, (v) enhance cooperation among group members during the preparation of the script, and (vi) is suitable as a research instrument. The results also found that in preparing the role play script (i) students are given enough time to prepare the script and practice, (ii) vocabulary given is sufficient to help students prepare the role play script, (iii) lecturers provide guidance in preparing the play script roles, (iv) the syllabus helps to prepare the script according to the theme and (v) the use of the application helps in the preparation of the acting script. Through the survey conducted, students also provided some suggestions for improvement to this assessment instrument.